Coping as a predictor of treatment outcome in people at clinical high risk of psychosis. Issue 1 (25th February 2014) - Kommescher, Mareike; Wagner, Michael; Pützfeld, Verena; Berning, Julia; Janssen, Birgit; Decker, Petra; Bottlender, Ronald; Möller, Hans‐Jürgen; Gaebel, Wolfgang; Maier, Wolfgang; Klosterkötter, Joachim; Bechdolf, Andreas
Abstract: Aim: The concept of coping is relevant to recent models of psychosis, and people with established psychotic disorders have been found to predominately use maladaptive coping strategies. This study aimed to examine the general coping patterns of people at clinical high risk of psychosis (CHR) and to investigate whether pre‐therapy coping behaviour plays a role in predicting responsiveness to early interventions. Methods: One hundred twenty‐eight help‐seeking CHR outpatients were randomized into two treatment groups: either receiving integrated psychological intervention (IPI), including cognitive behaviour therapy, or supportive counselling (SC) for 12 months. Of those, 91 persons completed a Stress Coping Questionnaire (SCQ) at intake: 45 in the IPI group and 46 in the SC group. General coping behaviour in this sample was analysed and several regressions were conducted separately for each treatment group to examine coping as a predictor of outcome after 12 months of different forms of treatment. Results: Participants relied significantly more on negative than on positive coping strategies, t (90) = −7.185, P  < 0.001, and within the positive strategies, stress control was the most preferred one, t (90) = 10.979, P  < 0.001. Several pre‐therapy coping strategies significantly predicted improvement in symptomatic outcome in both treatment groups, explaining between 16% and 25% of variance. The predictive value of coping was higher in the SC group. Conclusions: Maladaptive coping behaviours were found to emerge in the early stages of psychosis and coping behaviour contributed significantly to the prediction of post‐treatment symptom improvement. These findings indicate a need for psychosocial support and coping strategy enhancement in people at risk of psychosis.